A histological investigation of dental crown characters used in mosasaur phylogenetic analyses - Street, Hallie; LeBlanc, Aaron; Caldwell, Michael (Vertebrate Anatomy Morphology Palaeontology, 2021)
Mosasaur researchers have used varieties of tooth crown ornamentation as diagnostic and phylogenetic characters for decades. Such tooth crown features include facets, flutes, striations, serrated carinae, and coarse anastomosing texture. This study investigates the relative contribution of dentine and enamel to the development of these dental characters and assesses possible homologies between these structures. Histological analysis of isolated mosasaur teeth revealed that flutes and facets develop initially from the dentine, and the external enamel morphology we observe macroscopically mirrors the shape the underlying dentine. Striations combine underlying contributions from the dentine with additional and irregular enamel deposition that results strictly from amelogenesis. In both serrated carinae and anastomosing texture the border between the dentine and the enamel is smooth, and these external ornamentations form through variations in enamel development. Based on these observations, we infer that flutes and facets are part of a morphological spectrum and should not be treated as separate phylogenetic characters. Conversely, striations develop differently than flutes and facets, and should therefore be treated as a distinct character. We recommend referring to the “serrations” on mosasaur carinae as crenulations to differentiate these enamel-only structures from true denticles possessing a dentine core. Anastomosing texture can also coincide with significant apical thickening, both of which could be adaptations for processing hard-shelled prey. Care must be taken when using tooth crown features as diagnostic or phylogenetic characters because seemingly different morphologies can have similar developmental origins, and tooth morphology can be more closely tied to diet than to common ancestry.